Psychologically ready? Cases of EFL Elementary School Teachers’ Readiness to Teach English in Indonesia - Anggi Angraeni; Fazri Nur Yusuf (Universitas Pendidikan Indonesia, 2022)
In the implementation of Kurikulum Merdeka in Indonesian schools, there is a fundamental change related to the position of English as a subject. When previously English was considered a local content subject at elementary schools, in today's curriculum, it becomes compulsory for both primary to secondary levels of elementary. The policymakers should be intrigued whether elementary school teachers in Indonesia are ready to respond to this change. Accordingly, this study intends to investigate to what extent the participated teachers are ready to teach English in elementary school. The psychological dimension of readiness was the main concern. To address this issue, a narrative inquiry involving three elementary teachers, all teaching in fourth grade, served as the participants of this study. They wrote their personal stories with guiding questions comprising their experiences dealing with English, how they had responded to changes, and their educational backgrounds. Through deductive coding and data analysis, it revealed that the participants had different ways of responding to change, such as: conducting preparation, worrying, being optimistic. They had different educational major, that was predicted as a factor influence self-efficacy. They also had different experiences in dealing with their English proficiency. However, they believed that they were psychologically ready to teach English at Elementary schools. Result indicates that there is importance to further investigate more in-depth investigations that include other dimensions of readiness: behavioural and situational readiness.